2012
DOI: 10.1097/sla.0b013e318272df97
|View full text |Cite
|
Sign up to set email alerts
|

HAnd Suture Versus STApling for Closure of Loop Ileostomy (HASTA Trial)

Abstract: Hand-sewn anastomosis versus stapler ileo-ileostomy for ileostomy closure are equally effective in terms of postoperative bowel obstruction, with stapler anastomosis leading to a shorter operation time. Postoperative ileus after ileostomy reversal remains a relevant complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 18 publications
2
84
0
8
Order By: Relevance
“…To date, it remains unclear which technique should be preferred. Recently, one large multicenter randomized trial was published with a non-significant trend toward fewer obstructions by stapling [3]. There was no difference regarding complications while stapling resulted in a shorter operation time.…”
Section: Introductionmentioning
confidence: 93%
“…To date, it remains unclear which technique should be preferred. Recently, one large multicenter randomized trial was published with a non-significant trend toward fewer obstructions by stapling [3]. There was no difference regarding complications while stapling resulted in a shorter operation time.…”
Section: Introductionmentioning
confidence: 93%
“…The surgical technique employed for the ileal anastomosis has been widely studied, and various published randomized controlled trials (RCTs) compare handsewn vs stapled anastomoses [10,11] . In our study, when analyzing the surgical technique and related complications, we only found statistical significance between end-to-end anastomosis without resection and postoperative paralytic ileus.…”
Section: Discussionmentioning
confidence: 99%
“…Ileus and bowel obstruction are still a major concern after ileostomy closure, and studies on technical issues have been carried out to address the problem. Some published randomized controlled trials compared stapled with hand-sewn anastomosis [23,24] . From our results, stapled anastomosis was more frequently used in the standard group, which may have increased the total cost for this group (standard group, 33,564 ± 10,448 CNY vs. late group, 29,233 ± 10,661 CNY; p = 0.03).…”
Section: Discussionmentioning
confidence: 99%